Placental and Fetal Toxicity of Albendazole Sulphoxide in Wistar Rats - Teruel, Miriam (2003)
This work characterized the effects of albendazole sulphoxided (ABZSO) on placental and fetal parameters in Wistar rats on day 20of gestation. (ABZSO) was fed in laboratory chow at 0. 2.5. 5. 10. 20 or 30 mg/kg/d from day 6 to 15 of gestation on pregnant rats. Data of resorptions, placental and fetal characteristics and fetal skeletal malformations were recorded. Resorption percentages in the 20 and 30 mg/kg/d groups were significantly higher compared to the control group. Placentals of (ABZSO) treated rats had lowel weight and smaller size than untreated rats. The fetal weight and size were lower in the 5 mg/kg/d dose compared to no treatment. In the 5, 10 and 20 mg/kg/d groups, reductions in ossificationprocess were observed. ABZSO induced malformations and/or fetal death when orally administered to pregnant rats. This data contributes to characterization of the reproductive toxicity of ABZSO, the main active metabolite of albendazole.